2020
DOI: 10.1042/bsr20201601
|View full text |Cite
|
Sign up to set email alerts
|

CircSERPINE2 weakens IL-1β-caused apoptosis and extracellular matrix degradation of chondrocytes by regulating miR-495/TGFBR2 axis

Abstract: The dysregulated circular RNAs (circRNAs) are relevant to the development of osteoarthritis (OA). The circRNA serpin family E member 2 (circSERPINE2) is dysregulated in OA, while the role and mechanism of circSERPINE2 in OA are largely unknown. The aim of our research is to explore how and whether circSERPINE2 regulates interleukin-1β (IL-1β)-caused chondrocyte damage in OA. In present study, the chondrocytes (CHON-001 cells) were exposed to IL-1β to mimic the injury in OA. CircSERPINE2, microRNA-495 (miR-495)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…As noted earlier in this review, circSERPINE2 protects ECM metabolism and regulates the apoptosis of OA chondrocytes. Xia and colleagues 83 found that the overexpression of circSERPINE2 mitigated IL-1b-induced chondrocyte apoptosis by decreasing caspase-3. OAassociated miR-495 has been confirmed as a target of circSERPINE2, and TGF-b receptor 2 (TGFBR2) is targeted by miR-495.…”
Section: Roles Of Circrnas In Apoptosismentioning
confidence: 99%
“…As noted earlier in this review, circSERPINE2 protects ECM metabolism and regulates the apoptosis of OA chondrocytes. Xia and colleagues 83 found that the overexpression of circSERPINE2 mitigated IL-1b-induced chondrocyte apoptosis by decreasing caspase-3. OAassociated miR-495 has been confirmed as a target of circSERPINE2, and TGF-b receptor 2 (TGFBR2) is targeted by miR-495.…”
Section: Roles Of Circrnas In Apoptosismentioning
confidence: 99%
“…In addition, circRNA TMBIM6 promotes ECM degradation of OA-induced chondrocytes via the miR-27a/matrix metalloproteinase-13 (MMP-13) axis, according to Bai et al [ 21 ]. circRNA SERPINE2 reduces IL-1 β -induced apoptosis and ECM degradation of chondrocytes by regulating the miR-495/transforming growth factor-beta receptor 2 (TGFBR2) axis [ 32 ]. Furthermore, the functions of circRNAs also include protein kinase activity, glycosaminoglycan binding, endoplasmic reticulum membrane, and peptidyl-serine phosphorylation, which can be the focus of future studies on the mechanism of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Xiang et al [54] revealed the expression profile of circRNAs in OA through RNA sequencing and identified 122 cir-cRNAs of differential expression. Based on these studies, NT5C2 [8], DUSP5 [9], UBE2G1 [10], GCN1L1 [11], HIPK3 [12], VCAN [13], ASH2L [15], SEC24A [18], PRKCH [19,20], TMBIM6 [21], VWF [23], PLOD1 [23], COL6A3 [23], hsa_circ_7 [24,25], ATP9B [26], PSM3 [27], MSR [28], CDR1 [29], CDH13 [30], RNF121 [31], CSNK1G1 [33], DHRS3 [35], PTPRA [38], IQGAP1 [39], SCAPER [39], RP11-909M7.3 [39] , RSU1 [40] SERPINE2 [7,32], CDK14 [14], PDE4D [16], ANKRD36 [17], hsa_circ_9119 [22], EPS15 [26,34], ADAMTS6 [36], UNK [37,41] BioMed Research International VWF (hsa_circ_0025119) had the highest value (Figure 3, Tables 3 and 4), indicating a significant interaction between VWF and other circRNAs; also, additional functions and signaling pathways were detected in the BP. Therefore, we speculated that VWF (hsa_circ_0025119) is more feasible to be used as a...…”
Section: 2mentioning
confidence: 99%
“…As a conclusion, CircSERPINE2 attenuated IL-1β-caused apoptosis and ECM degradation of chondrocytes by regulating miR-495/TGFBR2 axis → new target for OA treatment. [ 232 ] miR-17-5p OA cartilage and IL-1β-induced chondrocytes: miR-17-5p↓ Fucosyltransferase (FUT)1↑ [ 233 ] miR-296-3p CircCDH13 contributes to OA pathogenesis by acting as a sponge of miR-296-3p and regulating the miR-296-3p-PTEN pathway. Silencing of CircCDH13: chondrocyte apoptosis↓, ECM catabolism↓, anabolism↑, in vivo: alleviated OA.…”
Section: Genetic Regulators Of Inflammatory/catabolic Gene Expressionmentioning
confidence: 99%